(untitled) - Celko , Joe (San Francisco, CA, 2006)
This book is not an in-depth look at particular subjects, but an overview of many subjects that will give the working RDBMS programmers a map of the terra incognita they will face—if they want to grow.
Keywords: SQL (Computer program language),OLAP technology,SQL(chương trình ngôn ngữ máy tính), Công nghệ OLAP